2008
DOI: 10.1016/j.neurobiolaging.2006.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Use it or lose it? SES mitigates age-related decline in a recency/recognition task

Abstract: An important goal of aging research is to determine factors leading to individual differences that might compensate for some of the deleterious effects of aging on cognition. To determine whether socio-economic status (SES) plays a role in mitigating age-related decrements in the recollection of contextual details, we categorized older participants into low-and high-SES groups. Event-related potentials (ERPs) and behavioral data were recorded in a picture memory task involving recency and recognition judgments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 80 publications
3
45
1
1
Order By: Relevance
“…One possible marker for such processes is the left frontal negativity [18]. Although the processes reflected by this negativity are not known with certainty [18,19,23], one possibility is that this activity reflects attentional control mechanisms that focus on task-relevant attributes of the stored memory traces. Older adults may have been able to bring these processes on line to inform their old/new decisions only after the items' memory strengths had been augmented by repetition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible marker for such processes is the left frontal negativity [18]. Although the processes reflected by this negativity are not known with certainty [18,19,23], one possibility is that this activity reflects attentional control mechanisms that focus on task-relevant attributes of the stored memory traces. Older adults may have been able to bring these processes on line to inform their old/new decisions only after the items' memory strengths had been augmented by repetition.…”
Section: Discussionmentioning
confidence: 99%
“…Recent ERP research has identified a sustained left-frontal negativity (600-1200 ms) in older but not young adults that has been observed for retrieval conditions that require the remembering of contextual (i.e. source) information from the study phase, suggesting that it may reflect compensatory activity [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that socioeconomic status is linked with cognitive performance (Evans and Kantrowitz, 2002;Fors et al, 2009;Hackman et al, 2010;Hackman and Farah, 2009;Kaplan et al, 2001;Nguyen et al, 2008;Santos et al, 2008), and is therefore an important mediator in the association between environment and cognitive health in older age (Czernochowski et al, 2008;Jefferson et al, 2011;Roe et al, 2007;Stern et al, 1999). Several studies have explored this association in relation to the area of residence (Beard and Petitot, 2010;De Deyn et al, 2011;Yen et al, 2009), but although it is intuitive that urban and rural areas may have socioeconomic differences (Chan et al, 2013;Russ et al, 2012), research has mainly focused on socioeconomic status in relation to neighbourhoods: Specifically, educational attainment, income, poverty, occupation, and deprivation at neighbourhood level are significantly associated with cognitive performance in older age (Aneshensel et al, 2011;Lang et al, 2008;Sheffield and Peek, 2009;Wight et al, 2006).…”
Section: Environmental Factors Associated With Socioeconomic Statusmentioning
confidence: 99%
“…It contains the memory of an event, as well as the temporal, perceptual, and spatial context in which the event took place; we remember not only what happened, but also when and where it happened, and what preceded and followed this event (Cabeza, Anderson, Houle, Mangels, & Nyberg, 2000;Czernochowski, Fabiani, & Friedman, 2008;Fouquet, Tobin, & Rondi-Reig, 2010;Vakil & Blachstein, 1994). The memory of these spatial, temporal, and perceptual features is referred to as source or context memory (the "when, where, how" memory) as opposed to the item or content memory (the "what" memory, Cabeza et al, 2000;Gagnon, Soulard, Brasgold, & Kreller, 2007).…”
mentioning
confidence: 99%
“…The memory of these spatial, temporal, and perceptual features is referred to as source or context memory (the "when, where, how" memory) as opposed to the item or content memory (the "what" memory, Cabeza et al, 2000;Gagnon, Soulard, Brasgold, & Kreller, 2007). This contextual memory has been repeatedly dissociated, both experimentally and clinically, from the memory of the event itself (Czernochowski et al, 2008;Schacter, Kaszniak, Kihlstrom, & Valdiserri, 1991).…”
mentioning
confidence: 99%